Observation on the Impact of Different General Anesthesia Techniques on Post-Operative Outcomes in Patients Undergoing General Anesthesia (The Planet, 2024)
Introduction: General anesthesia is a standard practice in surgical procedures, ensuring patient comfort and safety during surgery. However, the choice of anesthesia technique can vary, with options ranging from intravenous anesthesia, inhalation anesthesia, to total intravenous anesthesia (TIVA).  Preoperative decision-making for patients requires a long-term perspective. Objective: This study aimed to compare the anesthetic effects of propofol, sevoflurane, and desflurane in a cohort of 300 patients undergoing a common surgical procedure. Methods & materials: Patient demographics revealed comparable sample sizes, with Group A (propofol) exhibiting a mean age of 45 ± 5, Group B (sevoflurane) 47 ± 6, and Group C (desflurane) 42 ± 4. Gender distribution was relatively balanced across the groups. Intraoperative parameters such as the duration of anesthesia, blood loss, and intraoperative fluids varied slightly among the three groups. Results: Group A demonstrated a lower incidence of nausea and vomiting compared to Groups B and C. Postoperative outcomes, including time to extubation, pain levels, and length of hospital stay, displayed subtle differences. Statistical analyses, employing one-way ANOVA for continuous variables and chi-square tests for categorical variables, were conducted. Additionally, complications, such as respiratory issues, cardiovascular complications, and surgical site infections, were assessed. Conclusion: The findings suggest that propofol has to be associated with a lower incidence of nausea and vomiting, warranting further investigation into its potential advantages in improving perioperative outcomes.
Keywords: General anesthesia; postoperative; propofol; nausea and vomiting